EXPERIMENTAL AND MATHEMATICAL EVALUATION OF THE REFRIGERATION SYSTEM PERFORMANCE WITH DIFFERENT AMBIENT TEMPERATURE - Ahmed Abed Mohammed; Ali Abas Nasser (Journal of Engineering and Sustainable Development, 2017)
The present work includes two main parts. Firstly: the experimental part takes respect of the effect of changing the magnitude of supplied voltage to compressor, condenser air flow rate, and evaporator air flow rate on system performance. The effect of ambient temperature on system performance is also considered. The experimental study has been done on a split air- conditioner with a 1 TR nominal capacity. The experimental results show that reducing the supplied voltage to the compressor by 23% caused the refrigeration capacity and COP)tot to decrease by 7.7% and 5.7%, respectively and when condenser airflow was reduced by 35.8%, cause the refrigeration capacity and COP)tot to decrease by 1.6% and 7.1%, respectively. Also, the reduction of the evaporator airflow by 46.7%, the refrigeration capacity, and COP)tot decreased by 11.4% and 9.6%, respectively. Secondly, the theoretical part, in which a mathematical model has been developed for the vapor compression refrigeration cycle to predict the system performance under the various ambient temperatures. The mathematical model was performed using Matlab software. The comparison between the mathematical results and experimental results shows that the maximum deviation of condenser capacity, refrigeration capacity, power input to compressor, and COP is 1.75%, 3.2%, 3.34%, and 4.84%, respectively.